Nigam’s scoring system for acute appendicitis with high accuracy surpassing Alvarado scoring system - Nigam, Vinod Kumar; Nigam, Siddarth (International Surgery Journal, 2022)
Background: Acute appendicitis is one of the most common surgical emergencies. Delay in the treatment of acute appendicitis can result in complications, may be lethal. That’s why the early diagnosis and quick treatment is essential. The diagnosis of acute appendicitis is still a clinical one. Alvarado scoring system is the commonest scoring system but it has many lacunae. Nigam’s scoring system (NSS) is invented to deal with drawbacks of Alvarado scoring system and improve accuracy. Methods: NSS has 17 scoring points. This scoring system can be divided into three parts, 6 and below 6, 7 to 10, and 11 and above. This study includes 36 patients of acute abdomen during a period of 8 years from Jan 2012 to Jan 2020. The diagnosis of acute appendicitis by NSS was compared with the ultrasonography findings, operation findings, and histopathological results. Results: Out of 36 patients 2 patients scored 6 and below, 3 patients scored 7 to 10 and 31 patients scored 11 and above. Accuracy of NSS resulted in 100%. No negative appendicectomy was recorded. Conclusions: NSS has better accuracy than Alvarado scoring system in diagnosing acute appendicitis. NSS is an easy, economical, simple, accurate, fast and dependable scoring system. NSS is best suited for small hospitals which lack advance investigative techniques such as ultrasound, CT scan and MRI.